Lipid Mediators in Acne - Monica Ottaviani; Emanuela Camera; Mauro Picardo (Hindawi Limited, 2010)
Multiple factors are involved in acne pathogenesis, and sebum secretion is one of the main ones. The role sebum plays in acne development has not been completely elucidated yet; however, increasing amounts of data seem to confirm the presence of alterations in sebum from acne patients. Altered ratio between saturated and unsaturated fatty acids has been indicated as an important feature to be considered in addition to the altered amount of specific fatty acids such as linoleic acid. Furthermore, particular attention has been focused on squalene peroxide that seems to be able to induce an inflammatory response beyond cytotoxicity and comedones formation. Moreover, recent data suggest that lipid mediators are able to interfere with sebocytes differentiation and sebogenesis through the activation of pathways related to peroxisome proliferators-activated receptors. Understanding the factors and mechanisms that regulate sebum production is needed in order to identify novel therapeutic strategies for acne treatment.